18F-DOPA PET/CT in brain tumors: impact on multidisciplinary brain tumor board decisions. - Humbert, Olivier; Bourg, Véronique; Mondot, Lydiane; Gal, Jocelyn; Bondiau, Pierre-Yves; Fontaine, Denys; Saada-Bouzid, Esma; Paquet, Marie; Chardin, David; Almairac, Fabien; Vandenbos, Fanny; Darcourt, Jacques (European Journal of Nuclear Medicine & Molecular Imaging, 2019)
Purpose: This study aimed to assess the therapeutic impact and diagnostic accuracy of 18F-DOPA PET/CT in patients with glioblastoma or brain metastases.Methods: Patients with histologically proven glioblastoma or brain metastases were prospectively included in this monocentric clinical trial (IMOTEP). Patients were included either due to a clinical suspicion of relapse or to assess residual tumor infiltration after treatment. Multimodality brain MRI and 18F-DOPA PET were performed. Patients' data were discussed during a Multidisciplinary Neuro-oncology Tumor Board (MNTB) meeting. The discussion was first based on clinical and MRI data, and an initial diagnosis and treatment plan were proposed. Secondly, a new discussion was conducted based on the overall imaging results, including 18F-DOPA PET. A second diagnosis and therapeutic plan were proposed. A retrospective and definitive diagnosis was obtained after a 3-month follow-up and considered as the reference standard.Results: One hundred six cases were prospectively investigated by the MNTB. All patients with brain metastases (N = 41) had a clinical suspicion of recurrence. The addition of 18F-DOPA PET data changed the diagnosis and treatment plan in 39.0% and 17.1% of patients' cases, respectively. Concerning patients with a suspicion of recurrent glioblastoma (N = 12), the implementation of 18F-DOPA PET changed the diagnosis and treatment plan in 33.3% of cases. In patients evaluated to assess residual glioblastoma infiltration after treatment (N = 53), 18F-DOPA PET data had a lower impact with only 5.7% (3/53) of diagnostic changes and 3.8% (2/53) of therapeutic plan changes. The definitive reference diagnosis was available in 98/106 patients. For patients with tumor recurrence suspicion, the adjunction of 18F-DOPA PET increased the Younden's index from 0.44 to 0.53 in brain metastases and from 0.2 to 1.0 in glioblastoma, reflecting an increase in diagnostic accuracy.Conclusion: 18F-DOPA PET has a significant impact on the management of patients with a suspicion of brain tumor recurrence, either glioblastoma or brain metastases, but a low impact when used to evaluate the residual glioblastoma infiltration after a first-line radio-chemotherapy or second-line bevacizumab.